Impact of Uganda’s National Land Policy on women’s ownership, control, and decision-making rights over agricultural land holdings - Laird, Victoria M. (Kansas State University, 2020)
Property rights can transform individuals’ incentives and facilitate economic prosperity, especially in agriculture. For women, these opportunities are invaluable, but often constraints from overlapping legitimizing systems prevent women from realizing the same property rights as their male counterparts. Many governments have implemented land reforms to counteract this issue, yet other invisible infrastructures exert influence over the practice of women’s rights, preventing progress. If there is an external change in statutory rights for women, can change subsequently occur in their realized rights, impacting their economic opportunities? To examine this question, I analyze women’s land rights in the context of Uganda’s National Land Policy (NLP), a set of comprehensive land reforms reinforcing gender equality in statutory property rights, and its accompanying Implementation Action Plan, which initiates programs to enforce the policy, including gender sensitivity programs. If the programs were enacted and legal gender equality was enforced, I would expect women gained additional realized property rights. Using data from the World Bank’s Living Standards Measurement Survey in Uganda, I explore this relationship with two different identification strategies. The difference-in-difference model discovers if the treatment had an effect on women’s ownership, control, and decision-making rights over agricultural land holdings, while a modified difference-in-difference model examines how these rights changed as the time from policy implementation increased. The results show the treatment had no impact on women’s land rights, and increased exposure to treatment had no effect on outcomes as well. Therefore, these findings imply the policy implementation did not make progress towards gender equality in land rights, or the timeline is not long enough to capture the impact from these programs.
Keywords: Agricultural economics; Policy analysis; Property rights; Legal pluralism; Agricultural development; Uganda National Land Policy